EFEKTIVITAS PEMBERDAYAAN PETERNAK SAPI PERAH OLEH KUD MOJOSONGO DI DESA SINGOSARI - , RETNO WULAN N, Dr. Subandono Agus Margono ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Breeders in Singosari village face problems in economic aspect. KUD Mojosongo as institutions make a empowerment programs for responsible effort the breeders. The empowerment programs aimed for assistance breedersâs economic problem. Objective: This study aimed for to know breeders empowerment effect which done KUD Mojosongo Methods: The research is mix methods kulitatif research and kuantitatif research. Research location in Singosari village, mojosongo subdistrict, boyolali regency. Taking informant research are created based selection and research sample used simple random sampling. Results: KUD Mojosongo be a place institution constitute for the breeders to put outcame milk from the breeders. KUD Mojosongo a responsible institution for the breeders have important the rule of the breeders advance. Effort KUD Mojosongo done for help breedersâs economic problem with a empowerment programs. Outcame from breeder empowerment program can views from breedersâs daily life which more and more good and they can developing their effort. Conclusions: KUD Mojosongo effort through empowerment programs is enough effective because all effort appropriate with early goal namely empower and to the canging for breedersâs economic aspect in singosari village. Suggestions: 1. KUD must be intensive for socialization and to know more everyting breedesâs need. 2. With empowerment the breeders can be spirit.